2020
DOI: 10.1002/oby.22997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesogenic Medication on Weight‐ and Fitness‐Change Outcomes: Evidence from the Look AHEAD Study

Abstract: Objective This study evaluates whether obesogenic medications may decrease the effectiveness of lifestyle interventions. The authors of this study hypothesized that participants who took obesogenic medications would be less responsive to the intervention in the Look AHEAD trial. Methods In the trial, 5,145 participants with overweight or obesity, aged 45 to 76 years with type 2 diabetes, were randomly assigned to an intervention (vs. support and education). In this analysis, the association of exposure to obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… 11 Use of obesogenic medications is associated with lower chance of achieving successful weight loss after both behavioral interventions and bariatric surgery and may contribute to the obesity epidemic. 9 , 10 , 24 , 29 , 30 In response to these data, the Endocrine Society Clinical Practice Guidelines recommend leptogenic medications (i.e., medications that promote weight loss) and weight-neutral medications as alternatives to obesogenic medications for people with overweight or obesity. 11 However, our results showed that almost 40% of people with overweight or obesity took at least one obesogenic medication, even when there were non-obesogenic alternatives.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Use of obesogenic medications is associated with lower chance of achieving successful weight loss after both behavioral interventions and bariatric surgery and may contribute to the obesity epidemic. 9 , 10 , 24 , 29 , 30 In response to these data, the Endocrine Society Clinical Practice Guidelines recommend leptogenic medications (i.e., medications that promote weight loss) and weight-neutral medications as alternatives to obesogenic medications for people with overweight or obesity. 11 However, our results showed that almost 40% of people with overweight or obesity took at least one obesogenic medication, even when there were non-obesogenic alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Some medications are well known to produce weight gain, including antidiabetic and antidepressant drugs 17 . In the Look AHEAD study, if patients were exposed to one or more of these obesogenic medications then the probability of achieving a weight loss of greater than 5% was reduced by 32% 80 . If the patient interview identifies one or more of the drug classes listed in Table 2 then the healthcare provider can review the possibility of switching to drugs that have the least adverse effect on weight 17 …”
Section: Treatment Options To Help Patients Maximize Their Outcomesmentioning
confidence: 99%